Pengaruh Penyuluhan Kesehatan SADARI Sebagai Deteksi Dini Kanker Payudara Pada Mahasiswa - Anita Rahmiati Bur; Zakiyah St. (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2025)
Breast cancer is one of the leading causes of death among women worldwide and in Indonesia. Early detection is an essential strategy to increase survival rates, one of which is through SADARI (self-breast examination), a simple, inexpensive, and effective method. This study aimed to determine the effect of health education on students’ knowledge, understanding of objectives, and perceived benefits regarding SADARI as an early detection method for breast cancer. This research employed a quantitative design with a case-control study approach. The study population consisted of all students at AKBID Syekh Yusuf Al Makassari, Gowa Regency, totaling 50 respondents, using a total sampling technique. The results showed that the majority of students had good knowledge (90.0%), understood the objectives of health education (90.0%), and perceived the health education as beneficial (82.0%). Bivariate analysis revealed a significant relationship between knowledge (p = 0.040), understanding of objectives (p = 0.011), and perceived benefits (p = 0.000) with the practice of SADARI. The conclusion of this study is that health education has proven effective in improving students’ knowledge, understanding, and perceived benefits, thereby positively influencing the practice of SADARI as an early detection method for breast cancer. Similar educational interventions should be continuously enhanced as part of promotive and preventive efforts to reduce morbidity and mortality rates from breast cancer